Participation in the Preparation of Local Development Plans in the Area of Sahasakhan Subdistrict Administrative Organization, Sahasakhan District, Kalasin Province: Participation in the Preparation of Local Development Plans in the Area of Sahasakhan Subdistrict Administrative Organization, Sahasakhan District, Kalasin Province - Khamphamuang, Kamonchanok; Yupass, Yupaporn; Kenaphum, Sanya (RATANABUTH JOURNAL, 2025)
This research aimed to 1) study the level of participation in the preparation of local development plans in the area of Sahasakhan Subdistrict Administrative Organization, Sahasakhan District, Kalasin Province, 2) compare the participation in the preparation of local development plans in the area of Sahasakhan Subdistrict Administrative Organization, Sahasakhan District, Kalasin Province classified by gender, age, education level, occupation and income, 3) study the guidelines for creating participation in the preparation of local development plans in the area of Sahasakhan Subdistrict Administrative Organization, Sahasakhan District, Kalasin Province. The research sample consisted of 365 eligible voters aged 18 years and over using Taro Yamane's formula. The research instruments were rating scale questionnaires. The statistics used for data analysis were percentage, mean, frequency and standard deviation. The comparison of participation classified by gender was done using the T-test and classified by age, education level, occupation and village of residence using the one-way ANOVA. The research results found that 1) The level of participation in the preparation of local development plans in the area of Sahasakhan Subdistrict Administrative Organization, Sahasakhan District, Kalasin Province Overall, it is at a moderate level ( = 3.44, S.D. = 0.81) 2) Comparison of participation in the preparation of local development plans in the area of the Sahasakhan Subdistrict Administrative Organization, Sahasakhan District, Kalasin Province, classified by gender and education level. The participation was different at a statistically significant level of .05. The participation was not different according to age, occupation and village. 3) Guidelines for creating participation in local development plans include decision-making: Providing opportunities for all groups of people to participate in determining the direction through community forums and public hearings. Practice: Promoting the role of people in development projects and establishing monitoring mechanisms. Receiving benefits: Creating opportunities to access jobs, funding and welfare fairly and evaluation: Establishing a civil society committee, using easily accessible evaluation tools, and using suggestions to improve the plan.